2011
DOI: 10.1002/qj.882
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ice cloud representation in the ECMWF and UK Met Office models using CloudSat and CALIPSO data

Abstract: Ice cloud representation in general circulation models remains a challenging task, due to the lack of accurate observations and the complexity of microphysical processes. In this article, we evaluate the ice water content (IWC) and ice cloud fraction statistical distributions from the numerical weather prediction models of the European Centre for Medium-Range Weather Forecasts (ECMWF) and the UK Met Office, exploiting the synergy between the CloudSat radar and CALIPSO lidar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 33 publications
8
70
0
Order By: Relevance
“…8d-f show that HiGEM produces higher mean reflectivity from fewer clouds when compared to ERAI-which may indicate more precipitation being produced by the convection scheme in HiGEM than ERAI, though still not capturing the observed distributions. It has previously been shown that the ERAI cloud scheme fails to represent ice water content distribution in the −20 to 0 • C range, which can be reconciled with the underestimate of reflectivity in ERAI at upper levels (see Delanoë et al 2011) It is clear from the transects in Fig. 8 that in the CloudSat composite ETC, significant precipitation can occur both north and south of the axis of propagation, whilst precipitation in both HiGEM and ERAI mostly occurs towards the south, particularly in ERAI-an important finding in the context of the influence of latent heating in ETCs.…”
Section: Cloudsat Composite Storm Structurementioning
confidence: 93%
“…8d-f show that HiGEM produces higher mean reflectivity from fewer clouds when compared to ERAI-which may indicate more precipitation being produced by the convection scheme in HiGEM than ERAI, though still not capturing the observed distributions. It has previously been shown that the ERAI cloud scheme fails to represent ice water content distribution in the −20 to 0 • C range, which can be reconciled with the underestimate of reflectivity in ERAI at upper levels (see Delanoë et al 2011) It is clear from the transects in Fig. 8 that in the CloudSat composite ETC, significant precipitation can occur both north and south of the axis of propagation, whilst precipitation in both HiGEM and ERAI mostly occurs towards the south, particularly in ERAI-an important finding in the context of the influence of latent heating in ETCs.…”
Section: Cloudsat Composite Storm Structurementioning
confidence: 93%
“…There have been past comparisons of the ECMWF ice water content product to satellite measurements of cloud ice content (Li et al, 2007;Waliser et al, 2009;Wu et al, 2009;Delanoë et al, 2011). They show that while the ice content may be under-estimated, there is at least good spatial agreement between ECMWF and the satellite measurements.…”
Section: A New Ice-flux-based Parametrisation (Iceflux)mentioning
confidence: 99%
“…A key input to the retrieval algorithm is an observational error covariance matrix, which includes both instrument and forward-model errors Hogan, 2008, 2010). The resulting DARDAR (for li-DAR + raDAR) products contain the profiles of the ice cloud related parameters on a 60 m vertical grid, which have been used in a number of studies (Bardeen et al, 2013;Battaglia and Delanoë, 2013;Ceccaldi et al, 2013;Delanoë et al, 2011Delanoë et al, , 2013Deng et al, 2013;Eliasson et al, 2012;Gayet et al, 2014;Huang et al, 2012;Jouan et al, 2012Jouan et al, , 2014Mason et al, 2014;Stein et al, 2011a, b).…”
Section: Cloudsat Geometrical Profiling Product (Geoprof)mentioning
confidence: 99%